Denitrification mechanisms in the polar stratospheres - Toon, Owen B.; Turco, R. P.; Hamill, P. (1990)
Microphysical simulations suggest that the time required for nitric acid particles to sediment from the stratosphere is comparable to the time required for falling ice particles to incorporate nitric acid vapor from the vapor phase. Since nitric acid particles form earlier in the winter than ice particles, these simulations favor denitrification being a separate process from dehydration, with denitrification being due to nitric acid particles and dehydration due to ice particles. In the simulations, the column abundance of nitric acid is only depleted if temperatures low enough for nitric acid particles to exist extend to the altitude above which the column is measured. Such low temperatures are infrequent in the Arctic lower stratosphere, which may be the main reason that the Arctic stratospheric column shows little loss of nitric acid during winter, while the colder Antarctic stratospheric column shows a substantial loss of nitric acid.